Meaning and displaying. A semantic analysis of meaning attributions - Raimondi, Andrea (2024)
In both ordinary talk and philosophical discourse, people use such sentences as ‘‘Blume’ means flower’ and ‘‘brother’ means male sibling’ to describe the meanings of expressions. I call these sentences ‘meaning attributions’. This dissertation offers a semantic analysis of them. The reason for linguistic interest in meaning attributions concerns their complement position. The expression therein hosted occurs in a way that seems to fall outside the traditional use/mention distinction – as popularised in the analytic tradition by such notable figures as Tarski and Quine. In the first chapter, I pause on this issue and related ones, reviewing some of the existing (limited) literature on the topic. In the second chapter, I examine the view that meaning attributions abbreviate, or are somehow equivalent to, appropriate synonymy sentences, an example of which is ‘‘Blume’ means the same as ‘flower’’. According to this view, contrary to first appearances, the complement of a meaning attribution is mentioned. I present several arguments against this view. In the third chapter, I defend my original analysis. It consists of two theses. The first is that the expression superficially occurring in the complement position is truth-conditionally inert and only serves to raise to salience its meaning; the latter is referred to by a demonstrative pronoun figuring at a deep level of linguistic representation. The second thesis is that ‘means’ shapes the context of utterance for a meaning attribution to the effect that its demonstratum parameter is supplied by the meaning of the displayed expression, so that the hidden demonstrative obligatorily refers to that entity. I represent the context-shaping role of ‘means’ as a suitable contextual restriction and argue that this role is (an aspect of) the non-truth-conditional meaning of this predicate. In the fourth chapter, I suggest that the mode of analysis defended for meaning attributions can be extended to provide similar analyses for other sentences. These include certain attitude reports that have been largely ignored in the philosophical literature, namely, those using the so-called ‘quotative ‘be like’’. Finally, in the same chapter, I discuss the relationship between my theory of meaning attributions and Davidson’s paratactic view of (pure) quotations. In this context, I offer a preliminary sketch of how my theory might be fruitfully combined with a Davidson-style view of (pure) quotations to provide a theory of what I will call ‘liberalised quotations’.